Ketahanan tanaman padi terhadap nematoda puru akar (Melidogyne Graminicola)=The resistance of rice to root-knot nematode (Meloidogyne graminicola) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT The objective of the research was to study the resistance behaviour of several rice varieties and lines to Meloidogyne graminicola and their mechanism of resistance. Two sequentcial experiments were carried out , the first was screening for resistance of 25 rice varieties and 12 lines